واقع ومعوقات الإفصاح عن المسؤولية الاجتماعية للشركة (دراسة تطبيقية على عينة من الشركات الخاضعة لأحكام هيئة الأوراق والأسواق المالية السورية) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدف هذا البحث إلى التعرف على واقع ومعوقات الإفصاح عن المسؤولية الاجتماعية في الشركات الخاضعة لأحكام هيئة الأوراق والأسواق المالية السورية. لتحقيق غرض الدراسة تم جمع البيانات لـ 29 شركة مسجلة في الهيئة، أجاب مديروها على أسئلة الاستبيان، وتم تحليل بيانات الدراسة باستخدام النّسب المئوية، التكرارات، واختبار Wilcoxon Signed Ranks Test. أظهرت نتائج الدراسة أن الشركات السورية تدرج قضايا المسؤولية الاجتماعية في استراتيجيات عملها، كما أن الحكومة السورية عملت على إصدار العديد من القوانين التي تنظم وتوجه عمل الشركات في مجال المسؤولية الاجتماعية. على الرغم من ذلك، فقد أظهرت نتائج الدراسة أن كلاً من: ضعف التشريعات المتعلقة بالإفصاح عن المسؤولية الاجتماعية للشركة؛ ضعف ثقافة الشركة بمفهوم المسؤولية الاجتماعية؛ التكاليف التي تترتب عن الإفصاح والمتعلقة بـجمع ونشر المعلومات؛ والأثر السلبي لتكاليف الإفصاح على ربحية الشركة تشكل عائقا أمام إفصاح الشركة عن مسؤوليتها الاجتماعية.This research aimed to identify the reality and obstacles of corporate social responsibility disclosure in firms subject to the regulations of the Syrian Commission on Financial Markets & Securities. To achieve the purpose of the study, data was collected for 29 firms registered in the Commission whereby the managers of these firms responded to the questionnaire. Data was analyzed using percentages, frequencies, and Wilcoxon Signed Ranks Test.Results of the study showed that the Syrian firms include social responsibility issues in their work strategies, and that the Syrian government worked on the issuance of many laws that regulate and guide the work of firms in the field of social responsibility.However, the results also revealed that the weakness in legislations related to the disclosure of corporate social responsibility; the weakness in the firm’s culture towards the concept of social responsibility; the costs arising from disclosure and related to the collection and dissemination of information; and the negative impact of disclosure costs on the profitability of the disclosing firm are all obstacles toward corporate social responsibility disclosure.